Chronic care service delivery models for people living with type 1 diabetes in low- and lower-middle income countries: a scoping review protocol. Issue 11 (19th November 2020) - Noble, Christopher; Adler, Alma; Park, Paul H.; Bavuma, Charlotte; Worster, Devin; Bukhman, Gene
ABSTRACT: Objective: The objective of this scoping review is to map the published literature that describes the distribution and organization of chronic care service delivery models for people living with type 1 diabetes (PLWT1D) in low- and lower-middle-income countries (LLMICs). Introduction: Type 1 diabetes is an autoimmune condition commonly diagnosed in childhood and early adolescence; it cannot be prevented and is deadly without daily insulin injections. Among PLWT1D, the islet cells in the pancreas produce insufficient amounts of the glucose-regulating hormone, insulin, resulting in the need for chronic insulin replacement therapy. Epidemiological information regarding type 1 diabetes (T1D) is limited in LLMICs. Improving survival for PLWT1D in LLMICs requires early diagnosis and greater access to high quality chronic care service delivery models for T1D. The identification and reporting of service delivery model typologies for PLWT1D will allow for more specific research questions regarding individual typologies in subsequent systematic reviews. Inclusion criteria: The review will consider all types of literature on the organization and distribution of chronic care services for the management of PLWT1D provided out of facilities in LLMICs, published from 2000 to the present. Methods: The JBI methodology for conducting scoping reviews will be employed. The search will be implemented across PubMed, Embase, and Web of Science. Full texts of the publications selected will be reviewed and data will be extracted through a charting table. The findings will be charted to summarize the results.